Inhibitors of Aspartate Transcarbamoylase Inhibit Mycobacterium tuberculosis Growth - Du, Xiaochen; Sonawane, Vidhisha; Zhang, Bidong; Wang, Chao; de Ruijter, Bram; Dömling, Alexander S S; Reiling, Norbert; Groves, Matthew R (ChemMedChem, 2023)
Aspartate transcarbamoylase (ATCase) plays a key role in the second step of de novo pyrimidine biosynthesis in eukaryotes and has been proposed to be a target to suppress cell proliferation in E. coli, human cells and the malarial parasite. We hypothesized that a library of ATCase inhibitors developed for malarial ATCase (PfATCase) may also contain inhibitors of the tubercular ATCase and provide a similar inhibition of cellular proliferation. Of the 70 compounds screened, 10 showed single-digit micromolar inhibition in an in vitro activity assay and were tested for their effect on M. tuberculosis cell growth in culture. The most promising compound demonstrated a MIC90 of 4 μM. A model of MtbATCase was generated using the experimental coordinates of PfATCase. In silico docking experiments showed this compound can occupy a similar allosteric pocket on MtbATCase to that seen on PfATCase, explaining the observed species selectivity seen for this compound series.
Keywords: molecular docking; Mycobacterium tuberculosis; allosteric inhibition; aspartate transcarbamoylase; Escherichia coli; Humans; kyselina asparagová; Aspartic Acid; pyrimidine biosynthesis; lidé